Factors affecting professional identity formation of basic medical sciences teachers in Pakistan: a phenomenological analysis of interviews - Kiran, Faiza; Javaid, Arshad; Irum, Shazia; Zahoor, Asiya; Farooq, Fareeha (Frontiers in Education, 2024)
Introduction Teachers can perceive themselves as a true teacher and act as one only if they have a strong professional identity. This study aimed to identify factors that shape the unique professional identity of basic medical sciences teachers in Pakistan. Methods A qualitative study was performed using the concepts of phenomenology and purposive sampling. A 20-item text-based interview was conducted by sharing a Google Form link with basic medical sciences teachers from select institutions. Iterative data collection and analysis were performed until data saturation was attained. Results A total of 40 participants took part in the study. Nine categories were identified and grouped into two major themes: four personal and five environmental factors. Personal factors included characteristics, preferences, religious values, and professional development. Environmental factors included community of practice, students' feedback, administrative support, work environment, and societal apathy. Among these factors, aptitude, family preference or work-life balance, hard work, dedication, and effect on parenting were more evident in women. By contrast, passion, experience, complacency, and unique identity were the prominent factors. Discussion Community of practice [31 (77%)], passion for teaching [21 (52%)], students' feedback [18 (45%)], work-life balance [16 (40%)], and religious values [13 (32%)] were the primary positive contributors to the identity of basic medical sciences teachers. By contrast, poor administrative support [8 (20%)], negative work environment [11 (27%)], job dissatisfaction [7 (17%)], societal apathy [4 (10%)], and lack of opportunities for professional growth [6 (15%)] negatively impact the professional identity of basic medical sciences teachers.